Pseudomonas strains isolated from different environmental niches exhibit different antagonistic ability. Issue 5 (3rd September 2019) - Chiellini, Carolina; Lombardo, Katia; Mocali, Stefano; Miceli, Elisangela; Fani, Renato
Abstract : The antagonistic interactions between microorganisms in the environment seem to play a key role in determining the spatial structuring of bacterial communities. In this work, the antagonistic interactions among 82 strains belonging to different Pseudomonas species isolated from six different environmental niches have been investigated to check whether it might be related to the environmental niches and/or to the taxonomical affiliation. The bacterial panel included 20 strains from Echinacea purpurea (12 from roots, 8 from the rhizosphere), 19 from Phragmites australis, 20 from the Acquarossa river (13 and 7 from red and black epilithon, respectively), 9 strains from red epilithon of the "Infernaccio waterfalls", 5 Antarctic strains, and 9 strains from the Amazon rainforest. Data obtained revealed that 81 out of the 82 strains exhibited an antagonistic activity (even though at a different extent) and that the environmental characteristics, which also determine different adaptative strategies, might be the main factor affecting antagonism among bacteria, even more than taxonomy. Strains isolated from heavy metal enriched river biofilms were described as the most active, while endophytic and rhizospheric strains were the most sensitive. This research, representing the first report in which Pseudomonas bacterial strains isolated from different ecological niches have been tested for their interaction abilities, opens new perspectives in discovering putative new antimicrobial compounds from different (extreme) environments.